Diagnosis of male central hypogonadism during childhood - Grinspon, Romina (2021)
The diagnosis of male central (or hypogonadotropic) hypogonadism, typically based on low luteinizing hormone (LH) and testosterone levels, is challenging during childhood since both hormones are physiologically low from the sixth month until the onset of puberty. Conversely, follicle-stimulating hormone (FSH) and anti-Müllerian hormone (AMH), which show higher circulating levels during infancy and childhood, are not used as biomarkers for the condition. We report the case of a 7-year-old boy with a history of bilateral cryptorchidism who showed repeatedly low FSH and AMH serum levels during prepuberty. Unfortunately, the diagnosis could not be ascertained until he presented with delayed puberty at the age of 14 years. A gonadotropin-releasing hormone (GnRH) test showed impaired LH and FSH response. By then, his growth and bone mineralization were partially impaired. Gene panel sequencing identified a variant in exon 15 of FGFR1, affecting the tyrosine kinase domain of the receptor, involved in GnRH neuron migration and olfactory bulb morphogenesis. Testosterone replacement was started, which resulted in the development of secondary sexual characteristics and partial improvement of bone mineral density.This case illustrates the difficulty in making the diagnosis of central hypogonadism in boys during childhood based on classical criteria, and how serum FSH and AMH assessment may be helpful if it is suspected before the age of puberty, and confirm it using next-generation sequencing. The possibility of making an early diagnosis of central hypogonadism may be useful for a timely start of hormone replacement therapy, and to avoid delays that could affect growth and bone health as well as psychosocial adjustment.